Planlı dönemde konsolide bütçe içinde sağlık hizmetlerinin finansmanı - Akgün, Semih (My University, 1999)
The current health condition and medical problems of Turkish population reveal the important aspect of health services in our country ,and reflect the fact that health policy is not established clean -cut adequately. Although some progress has been registered in Turkish health sector during the planned development period , there are still striking inequalities in interregion and intercity health condition ,fertility level and basic health services approach . When the relationship between the public health and econmomical development and their reciprocal influences are taken into account as regards our country's health problems ,it is seen that such relationship moves in a negative direction .As the nature of health environment involves the provision of preventive health services as well as the channelling of health spending favorably toward that service area ,the situation in Turkey is just the opposite. Limited implementation of socialization scheme recommended for the provision of basic health services has pushed people to apply to hospitals for all medical services, and this,in turn ,has given rise to inappropriate demand at hospitals , and , as a result of this fact ,the treatment oriented ( curing ) aspect of socialization has disappeared and, for that account , a larger share has been allocated to treatment - oriented health service spending .Nevertheless , preventive health services are provided free of charge in view of it's great importance ,which is why larger funds are necessary for this approach . Consequently , the main issue in health sector can be fixed as ensuring the efficiency of distribution systems in respect of health service availability in order to be able to improve the general health condition of the soceity . At this stage of the thesis ,I will try to put forward some ideas in respect of the measures which I deem necessary for making health services in Turkey efficient and effective .Our studies regarding the targets and policies show that the health policy targest have been fixed without making concrete determinations as regards planning and funds , and, sometimes , policies have been implemented in a manner which is different from that which had been established .For example , although the Goverment targeted to decrease the number of minor inpatient treatment units , we faced an increase in the number of such units . Good follow-through of the implementations required for achieving yhe targets is likely to improve the efficiency of health policy . In order to be able to achieve the goals in respect of general health service in a more efficient way ; it is necessary taht the factors establishing Turkish health systems should not be directed only in line with their own targets and that due consideration should be given to the operations of other units of health sector as well .Otherwise, the contribution of health sector spending to socio-economical development is doomed to remain weak . Development of investment planning method should not be considered for health sector only , and it is important to prove the necessity of big projects in sub-sectoral levels as well ,as well as to monitor the implementation thereof .The dispatch system launched with the reorganization of health system , patient acceptance policy , and improvement of hospital efficiency measurement are factors designed to decrease the need to build new hospitals significantly . The effectiveness of basic health services is thwarted by the inadequate number of medical human-force , the inadequate hospital equipment and health service vehicles as well as by the inadequate supply of medicines . Another factor lowering down the level of efficiency is teh fact that medical staff are appointed frequently ,thereby impairing their service motivation . The cost of public and private helth services is not known exactly ,and only expenditures are monitored . Hospital charge tariffs should be re-structured by establishing a solid base for real cost analysis . Accordingly , the level of charge tariffs applied by the public institutions may be adjusted in such a way that a regular and continual finance is provided depending on the nature of health service offered . Finally ,I would like to deal with the Draft Law Concerning the General Health Insurance and the new arrangements contemplated to be launched by said Law. Helath policy as set out in the 6th 5-year Development Plan had established goals in favour of the development of private sector in health services and the implementation of health insurance .This policy should not exert supply-squeezing influence on public health services , and the public sector's fundamental responsibility for the handling of preventive health services should be maintained exactly in order to further the health conditions .It is essential that the works relating to the General Health Insurance project designed to ensure an efficient use of the funds thanks to an organization under which all public health insitutions would gather should be handled in an excellent way . Whether preventive or treatment -oriented , the health services are regarded to be a part of the social infrastructure . When the general health insurance is involved , it would be necessary taht the health-related spending be increased considerably for being able to make the system go and run. Because it is true that the healthcare needs of the huge mass of uninsured people living generally in rural areas and having no awareness of social security concept and no income to pay for insurance premium would be met and handled on the strength of public funds . Furthermore , since a cooperation between yhe public and private sectors in spreading health service supply is in question , the fact taht private sector would increase the cost of health service that they offer should be taken into account as well .

Türkiye nüfusunun bugün içinde bulundugu sağlık durumu ve sağlık sorunları ülkemizdeki sağlık hizmetleri düzetyinin önemli boyutları ortaya çıkartmta ve sağlık polittttikalarının yeteri kadar açık belirlenmedigi gerçeğini yansıtmaktadır. Türkiye'de sağlık sektöründe planlı dönem içinde gelişmeler sağlanmış ise de ülke düzetinde bölgelerarası, kentlerarası sağlık durumu, dogurganlık düzeyi ve temel sağlık hizmetleri yaklaşımında hala çarpıcı eşitsizlikler vardır. Halk sağlığı ve iktisadi kalkınma arasındaki ilişki ve karşılıklı olarak birbirlerini etkileme durumu ülkemiz sağlık sorunları açısından ele alındığında bu ilişkinin olumsuz yönde geliştiği görülmektedir. Sağlık ortamının niteliği koruyucu sağlık hizmetlerinin verilmesini ve sağlık harcamalarının bu hizmet lehine dönüştürülmesini gerektirirken Türkiye'de durum tersine gelişmektedir. Temel sağlık hizmetleri verilmesi için önerilen sosyalizyon uygulamasının yeterince yaygınlaştırılması bütün sağlık hizmettleri için hastaneler başvurulmasına ve hastaneler gereksiz talebin oluşmasına neden olmuş, sosyalizasyonun tedavi edici boyutu kalkmış dolayısıyla tedavi edici sağlık hizmeti harcamalarına daha fazla pay ayrılmıştır. Halbuki koruyucu sağlık hizmetlerinin önemi gerği, topluma ücretsiz sunulması bu konuya ayrılacak kaynağın daha fazla olmasını gerektirmektir. Sonuç olarak sağlık sektörünün temel sorunu, toplumun genel sağlık durumunun iyileştirilmesi için; sağlık, beslenme durumu, dogurganlık ve temel sağlık hizmetlerinden yararlanma konularında dagıtım sisteminin etkiliğini sağlamak olarak belirlenebilir. Tezin bu aşamasında Türkiye'de sağlık hizmetlerinin verimli ve etkin bir hale getirilmesi amacıyla alınmasında yarar gördüğümüz önelemlere ilişkin düşünceler sunulmaya çalışılacaktır. Hedefler ve politikalar hakkındaki incelemelerimiz göstermiştirki; planlama ve kaynaklar açısından somut belirlemeler yapılmadan sağlık politikası hedefleri saptınmıştır ve bazen politikalar hedeflenenden gfarkıl şekilde uygulanmıştır. Örneğin küçük çaplı yataklı tedavi birimlerinin azaltılması hedef olarak saptanmışken aynı dönemde bu tür birimlerin sayısında artış görülmektedir. Belirlenmiş hedeflere ulaşılması için gereken uygulamaların iyi izlenmesi, sağlık politikasının etkinliğini artıracaktır. Genel sağlık sistemini oluşturan unsurlar yalnızca kendi hedefleri doğrultusunda yöneltilmemeli, sağlık sektörünün diğer birimlerinin faaliyetleri de göz önünde bulundurulmalıdır. Aksi halde sağlık sektörü harcamalarının sosyo-ekonomik gelişmeye katkısı beklenenden cılız kalır. Yatırm planlaması yönetiminin geliştirilmesi sadece sağlık sektörü için düşünülmemeli alt sektördüzeylerinde de büyük projelerin gerekliliğinin kanıtlanması ve uygulamalarının izlenmesi önemlidir. Sağlık sisteminin reorganizasyonu ile getirilen sevk sistemi, hasta kabul politikası, hastane verimlilik ölçümü ile mevcut hastane kullanımının artırılması yeni hastane yapımına duyulan gereksinimi önemli oranda azaltacaktır. Temel sağlık hizmetlerinin etkinliği; sağlık-insan gücü açığı, hastane donanımı, sağlık hizmet araçları ve ilaç eksikliği ile engellenmektedir. Ayrıca sağlık personeli atamalarının hareketli olması nedeniyle hizmete motivasyonlarının sağlanmaması verimliliği azalmaktadır. Kamu ve özel sağlık hizmetlerinin maliyeti tam olarak bilinmemekte sadece harcamalr izlenmektedir. Gerçek maliyet analizi için sağlam bir istatistiksel taban bulunarak, hastane üçret tarifelerinin yapısı yeniden gözden geçirilmelidir. Buna göre kamu kuruluşlarında uygulanan ücret tarifesinin düzeyi verilen sağlık hizmetinin niteliğine göre düzenli ve sürekli finansman sağlayacak biçimde ayarlanabilir. Son olarak Genel Sağlık Sigortası Kanun Tasarısı ve bu tasarı ile geterilmesi düşünülen yeni düzenlemelere dğinmek istiyorum. VI. Beş Yıllık Kalkınma Planında sağlık politikasının sağlık hizmetlerinde özel sektörün gelişmessini ve sağlık sigortası uygulamasını destekleyen doğrultuda saptanmış hedefleri bulunmaktadır. Bu politikanın kamu sağlık hizmetlerindeki arzı kısıcı etkisi olmamalı, sağlık koşullarının iyileştirilmesi için koruyucu sağlık hizmetleri programlaarının, yürütülmesinde kamunun temel sorumluluğu aynen korunmalıdır. Tüm kamu sağlık kuruluşlarını aynı çatı altında toplayacak bir örgütlenmeyle kaynakların etkin kullanımı sağlamayı amaçlayan Genel Sağlık Sigortası projesi çalışmalarının çok iyi yapılması zorunludur. Ister koruyucu ister tedavi edici sağlık hizmeti şeklinde olsun hizmetleri sosay altyapı niteliğindedir. Genel sağlık sigortası söz konusu olduğunda sistemin işlemesi için kamunun sağlıkla önemli ölçüde artırması gerekecektir. Çünkü sigortasız, genellikle kırsal alanda yaşayan ve sosyal güvenlik konusunda bilgisi olmayan, sigorta primi ödeyecek gelirden yoksun kitlenin sağlık ihtiyaçları kurumsal finansman desteği ile yürülecektir. Ayrıca sağlık hizmetinin arzının genişletilmesinde kamu ve özel sektör işbirliği söz konusu olduğunda özel sektörün verilecek sağlık hizmetinin maliyetini artırıcı riski göz ardı edilmemelidir.
Keywords: FİNANSMAN; Fiziksel hastalık ve verilen hizmetler; SAĞLIK HİZMETLERİ; Toplumsal refah sorunları